GENDER REPRESENTATION IN ENGLISH TEACHING VIDEOS ON YOUTUBE FOR JUNIOR HIGH SCHOOL STUDENTS - Marpaung, Tiara Azzahra; Dewi, Anggun Citra Sari; Sasmita, Ruwaiza (ENGLISH JOURNAL, 2025)
Gender representation in learning media is one of the most important issues that measure the equality of appearance between male and female characters. The aim of this study is to find out whether male and female characters are represented equally and how male and female roles are described in the illustration of the selected learning videos. This study used mixed method, with quantitative applied to calculate the percentage of female and male. Qualitative is used to describe content analysis based on the roles of female and male. The objects are the selected English learning videos for Junior High School published in a well-known account, Ruangguru channel on Youtube. The number of characters reflecting male and female was classified by adapting from Stockdale in Miranda & Nurbatra (2019). The result of this study revealed that in three categories, the amount of male and female characters that arise is balanced with a percentage of 50% each. Meanwhile, in one category there are significant differences between female characters with 58% and male characters with 42%. It is concluded the gender representation in the five English learning videos was quite balanced. Moreover, female and male characters can be found together in the given conversation illustrations.